Infrared Thermal Images of Solar PV Panels for Fault Identification Using Image Processing Technique - V. Kirubakaran; D. M. D. Preethi; U. Arunachalam; Yarrapragada K. S. S. Rao; Mansour K. Gatasheh; Nasrul Hoda; Endalkachew Mergia Anbese (International Journal of Photoenergy)
Among the renewable forms of energy, solar energy is a convincing, clean energy and acceptable worldwide. Solar PV plants, both ground mounting and the rooftop, are mushrooming thought the world. One of the significant challenges is the fault identification of the solar PV module, since a vast power plant condition monitoring of individual panels is cumbersome. This paper attempts to identify the panel using a thermal imaging system and processes the thermal images using the image processing technique. An ordinary and thermal image has been processed in the image processing tool and proved that thermal images record the hot spots. Similarly, the new and aged solar photovoltaic panels were compared in the image processing technique since any fault in the panel has been recorded as hot spots. The image recorded in the aged panels records hot spots, and performance has been analyzed using conventional metrics. The experimental results have also been verified.